Ordered self-assembly of amphipathic graphene nanosheets into three-dimensional layered architectures. Issue 1 (8th December 2015) - Fang, Qile; Zhou, Xufeng; Deng, Wei; Liu, Zhaoping
Abstract : A novel layered three-dimensional graphene-based architecture is achieved via an ordered self-assembly process, which possesses favorable microchannels for mass transfer. Abstract : A novel layered graphene-based architecture is achieved via an ordered self-assembly process. Amphipathic graphene nanosheets are joined horizontally into large sheets via edge splicing, and a cross-linking agent of poly(vinyl alcohol) bridges them into integrated three-dimensional monoliths with tunable interlayer spacing. This layered architecture possesses highly ordered and favorable microchannels for molecular transfer.